2007
DOI: 10.1038/sj.onc.1210563
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the RNA-binding protein IMP1 correlates with poor prognosis in ovarian carcinoma

Abstract: The IMP (IGFII mRNA-binding protein) family comprises a group of three RNA-binding proteins involved in the regulation of cytoplasmic mRNA-fate. Recent studies identified IMP proteins as oncofetal factors in various neoplasias, but knowledge of a potential role in ovarian carcinomas is still lacking. The immunohistochemical analysis of 107 ovarian carcinomas, 30 serous borderline tumors of the ovary and five normal ovaries revealed de novo synthesis of IMP1 in 69% of ovarian carcinomas. Elevated IMP1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
108
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(129 citation statements)
references
References 24 publications
16
108
1
Order By: Relevance
“…IGF2BP1 is expressed during embryogenesis, but this protein is also synthesized in a broad variety of malignancies (33). The expression of IGF2BP1 was associated with an overall poor prognosis in a wide range of cancers, suggesting that the protein may act as a potent oncogenic factor (34,35). Accordingly, we observed that IGF2BP1 expression was up-regulated in tumor tissue (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…IGF2BP1 is expressed during embryogenesis, but this protein is also synthesized in a broad variety of malignancies (33). The expression of IGF2BP1 was associated with an overall poor prognosis in a wide range of cancers, suggesting that the protein may act as a potent oncogenic factor (34,35). Accordingly, we observed that IGF2BP1 expression was up-regulated in tumor tissue (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, the survival and proliferation genes CDC25A, Myc, and Src, which we identified as indirect downstream targets for triptolide, have previously been identified as important oncogenic regulators of acute myeloid leukemia (46)(47)(48). Myc has also been described to be directly involved in the tumorigenicity of ovarian, colon, and esophageal cancers (48)(49)(50)(51). Altogether, these results represent a breakthrough toward the potential therapeutic benefits from a triptolide-based therapy in cancer.…”
Section: Discussionmentioning
confidence: 54%
“…Members of the protein family show an oncofetal expression declining toward the end of embryogenesis, barely detectable expression in the postnatal phase, but rapid de novo synthesis in various neoplasias (Nielsen et al 1999;Yaniv and Yisraeli 2002;Kobel et al 2007).…”
Section: Introductionmentioning
confidence: 99%